2015
DOI: 10.1016/j.bjid.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and epidemiology of cefoxitin resistance among Enterobacteriaceae lacking inducible chromosomal ampC genes from hospitalized and non-hospitalized patients in Algeria: description of new sequence type in Klebsiella pneumoniae isolates

Abstract: In this study, 922 consecutive non-duplicate clinical isolates of Enterobacteriaceae obtained from hospitalized and non-hospitalized patients at Bejaia, Algeria were analyzed for AmpC-type β-lactamases production. The ampC genes and their genetic environment were characterized using polymerase chain reaction (PCR) and sequencing. Plasmid incompatibility groups were determined by using PCR-based replicon typing. Phylogenetic grouping and multilocus sequence typing were determined for molecular typing of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
(74 reference statements)
2
4
0
Order By: Relevance
“…Our findings are consistent with previous reports noting the predominance of CMY worldwide [ 30 - 32 ]. In accordance with the earlier study in Tunisia reported the coexistence of various bla AmpC genes in a single strain and of such coorcurrence in several species in Enterobacteriaceae [ 33 ], multiple AmpC genes were detected in one-third of isolates: one isolate expressing bla CMY and bla EBC genes co-exist together, the other two isolates co-expressing bla CMY and bla MOX genes. However, in 5/9 isolates only one AmpC gene was detected bla CMY , bla MOX or bla DHA .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with previous reports noting the predominance of CMY worldwide [ 30 - 32 ]. In accordance with the earlier study in Tunisia reported the coexistence of various bla AmpC genes in a single strain and of such coorcurrence in several species in Enterobacteriaceae [ 33 ], multiple AmpC genes were detected in one-third of isolates: one isolate expressing bla CMY and bla EBC genes co-exist together, the other two isolates co-expressing bla CMY and bla MOX genes. However, in 5/9 isolates only one AmpC gene was detected bla CMY , bla MOX or bla DHA .…”
Section: Discussionsupporting
confidence: 90%
“…These findings underscore previous results reported in literature stating that use of one of the two antibiotic classes allows a co-selection process [7,8,21]. In Algeria, PMQR genes were reported from clinical human isolates both in hospital and community and were frequently associated with bla CTX-M genes [30,35].…”
Section: Discussionsupporting
confidence: 86%
“…It is noteworthy to mention that cefoxitin (a second-generation cephalosporin) was once considered as an alternative if the bacterial strain developed resistance towards other second-generation cephalosporins, due to its resistance towards β-lactamase/cephalosporinase [ 45 ]. However, past reports suggested that bacterial strains have gained resistance towards cefoxitin as well by alternate mechanisms [ 6 , 7 , 46 , 47 , 48 ]. It has been reported that cefoxitin resistance in K. pneumoniae and E. coli is linked with porins or non-specific outer-membrane proteins ompK35 and ompK36 [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%